Internal and external influences on role stereotype adherence and gender dynamics on engineering design teams - Anastasia M. Schauer; Jessie Liu; Christopher Saldaña; Katherine Fu (International Journal of STEM Education)
Abstract Background Even among women who persist in the gender-imbalanced engineering fields, women on engineering design teams tend to take on non-technical roles. Understanding the mechanisms that inform this phenomenon is important for encouraging more women in STEM in order to close the gender gap. Although factors such as self-efficacy, task allocation, and occupational prestige have previously been examined through a gender-based lens, this study considers all of these factors together in order to better understand the role of internal and external effects on role stereotype adherence in engineering design teams. A survey was administered to computer science and engineering students in the United States presenting a scenario in which they are members of an engineering design team. Participants reported their interest, self-efficacy, and anticipated contribution to the project. All participants were then assigned a documentation role by a teammate and asked the same questions again after a brief reflection. Results While all participants exhibited higher interest in a more socially impactful project, participants’ interest in the project decreased significantly after they were assigned the non-technical, feminine-stereotyped role of documentation. Women reported significantly higher experience, interest, and self-efficacy levels in documentation compared to men. After being assigned the documentation role, men anticipated that their contribution to the project would be significantly lower compared to women, indicating a decrease in interest or a devaluation of their role on the team. Perceived sexism may have also played a part in how women reacted to role allocation, as it is hypothesized that reactance theory led women’s interest in a mechanical design role to increase post-role allocation. Conclusions These results support existing literature related to the likelihood of (1) women taking on non-technical roles on engineering teams and (2) society devaluing work that is stereotypically associated with feminine stereotypes. Participants’ reactions to role allocation were most closely related to internal factors, such as self-efficacy and the implicit devaluation of femininity. Findings can be used to inform curriculum development in hands-on design project courses and management of design groups in industry.